Morphometric analysis of the red fox molar teeth in Lithuania. (3rd May 2022) - Jurgelėnas, Eugenijus; Jasinevičiūtė, Indrė; Kerzienė, Sigita; Daugnora, Linas
Abstract: The objective of the study was to investigate the lengths and widths of maxillary (P 4, M 1 and M 2 ) and mandibular (M1, M2 and M3 ) molar teeth, lengths of dental rows and dental features of sexual dimorphism in the red fox. The correlation analysis between teeth measurements and dental row length was included too. The osteometric analysis was performed by the A. von den Driesch (1976) method. A total of 230 skulls and mandibles were investigated ( n  = 230): 113 males ( n  = 113) and 117 females ( n  = 117). The findings of the research revealed that most dimensions are higher in males compared with females ( p  < 0.001). Contrarily, Wilks' Lambda analysis showed results in the interval from 0.821 to 1, which leads to the conclusion that a teeth measurement study is unreliable to determine the sex of the red fox. The trustworthy measurements were the length of the whole dental arcade in the maxilla and mandible (UDR and LDR); Wilks' Lambda UDR = 0.860; LDR = 0.821; p  < 0.001). Evaluation of the correlation between measurements revealed that results vary from very weak (0.047) to moderate strength (0.543). There were no strongly correlating measurements found. The correlation between the upper and lower molars with the length of the teeth arcade is quite weak, and only solitary measurements (M 2, L and B) had a weak correlation.